Determinants of Immediate Essential Newborn Care Practice in Eastern Rural Nepal - Dahal, Ramesh Kumar (International Journal of Child Health and Nutrition, 2013)
Neonatal mortality remains high in Nepal. Improvement in immediate essential newborn care practices such as "use of clean instrument to cut the umbilical cord ”, "drying and wrapping the baby before placenta was delivered”, "initiation of breastfeeding within an hour of delivery" and "first bathing of neonate after 24 hours of delivery" can reduce neonatal deaths. However, this can only be accomplished if factors associated with reduced neonatal mortality can be identified. A regional study was carried out with 252 randomly selected women having child aged 11 months or younger; of which about 70 percent, 18 percent and 20 percent had received delivery assistance with skilled birth attendant, trained health professional and untrained friend/relatives respectively. Skilled Birth Attendant appeared as the determinant of the use of clean instrument to cut the umbilical cord (OR=164.33), first bathing of neonate after 24 hours of delivery (OR= 5.14) and drying and wrapping the baby before placenta was delivered (OR= 50.75) whereas Trained Health Professionals turned out to be the determinant of the use of clean instrument to cut the umbilical cord (OR=3.81) and first bathing of neonate after 24 hours of delivery (OR=3.14) only (Reference: Untrained relatives/friends). Maternal age (OR= <20:10.59 and 20-30: 6.39; Ref: >30 years) and education (OR=Primary-21.81; Secondary-20.11; Ref-Higher) appeared the determinant of initiation of breastfeeding within an hour of delivery. The time gap between delivery and the mother receiving the baby was also significantly positively associated with initiation of breastfeeding within an hour of delivery. This result indicates the need to increase the coverage of health facilities which can provide SBA, empower women to involve a SBA in delivery and provide newborn care education to women and family members. In order to better understand how to decrease neonatal mortality, further study should focus on understanding why there were better newborn care practices in births assisted by a SBA than THPs.